The Illocutionary Acts Found In Uncharted Movie - Ni Kadek Sinta Dewi; I Wayan Budiarta (PRAGMATICA : Journal of Linguistics and Literature, 2026)
This research is titled “The Illocutionary Acts Found in Uncharted Movie”. The source of data used in this research is the Uncharted movie. This research is qualitative.  The main theory used to classify the types of illocutionary acts applied by Searle's theory is taken from the book Expression and Meaning: Studies in The Theory of Speech Acts (1979). Analyzing the function of illocutionary acts is supported by Leech's theory, taken from the book Principles of Pragmatics (1983). The data collection method consisted of watching films carefully and repeatedly. After that, the taking note technique is applied in the dialogue of every character in the film, which contains illocutionary acts. Subsequently, the data were classified on the basis of the types of illocutionary acts, and the functions of each type was identified based on the theory applied. Afterwards, the data were analyzed descriptively on the basis of the types of illocutionary acts and the function of each type of illocutionary act. The finding of the research demonstrates the existence of four categories in the Uncharted movie, including assertive, directive, expressive, and commissive. It has four functions contained in film, including competitive, convivial, collaborative, and conflictive.